PENGELOLAAN WAKAF UANG DI BAITULMÃL MUAMALAT DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Suhairi, Suhairi (JURNAL PENELITIAN KEISLAMAN, 2011)
Muslims in Indonesia have been practicing cash endowment prior to the enactment of the Act No. 41 of 2004. It is therefore interesting to examine how this endowment has been managed by BMM and analyze it from the perspective of Indonesian law. The BMM has managed cash endowment since 2002. The primary data of this research was collected through interviews while the secondary data were gained from documentation. The analysis was deductively conducted by examining the compatibility of cash donation management with the provision of the state regulation. The management of cash endowment in BBM is not totally in line with the existing regulation especially regarding declaration of intent (ikrar) and the waqf certificate. Nevertheless, the investment aspect of waqf managed in BMM has met the regulation in that it at least keeps the nominal value but not the capital money. In terms of the usage of the endowment outcome, the cash donation has met with the state regulation although the money has only been used little for investment.